Image Processing using Pulse-Coupled Neural Networks Applications in Python - Lindblad, Thomas; Kinser, Jason M.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
Image processing algorithms based on the mammalian visual cortex are powerful tools for extraction information and manipulating images. This book reviews the neural theory and translates them into digital models. Applications are given in areas of image recognition, foveation, image fusion and information extraction. The third edition reflects renewed international interest in pulse image processing with updated sections presenting several newly developed applications. This edition also introduces a suite of Python scripts that assist readers in replicating results presented in the text and to further develop their own applications.
Biological Models -- Programming in Python -- NumPy, SciPy and Python Image Library -- The PCNN and ICM -- Image Analysis -- Feedback and Isolation -- Recognition and Classification -- Texture Recognition -- Color and Multiple Channels -- Image Signatures -- Logic.
Keywords: Engineering; Computer vision; Biomedical engineering; Engineering; Signal, Image and Speech Processing; Image Processing and Computer Vision; Biophysics and Biological Physics; Biomedical Engineering; Numerical and Computational Physics; Computer Imaging, Vision, Pattern Recognition and Graphics